Assessment practice of English language teachers in Myanmar - Zarni Mar (Journal of Green Learning, 2022)
Good assessment practices benefit both students and teachers in several ways: They give information to help teachers determine the appropriateness of content and the pace of the lesson. They also help teachers monitor student learning throughout the course. This research is set up to explore teachers’ perceptions of assessment in order to determine their beliefs, attitudes and views that affect their assessment practices. It also seeks to determine whether there are significant differences in teachers’ perceptions of assessment by gender. Data were collected from a questionnaire survey with 130 teachers. Teachers’ perceptions of assessment were measured through a calculation of the percentage, mean and standard deviation. The findings revealed that university teachers who participated in the research reported favorable and positive perceptions of assessment. Participants considered the ultimate goal of assessment is to evaluate students’ learning progress followed by to make decisions on teaching and learning. Most of the teachers also perceived that the basic role of assessment is to raise students’ learning and teaching practices. Furthermore, role-play is the most favored type of activities used for conducting assessment by English language teachers and teacher assessment was maintained by a large proportion of the participants.